2020
DOI: 10.1371/journal.pone.0230149
|View full text |Cite
|
Sign up to set email alerts
|

Delta neutrophil index for predicting mortality in trauma patients who underwent emergent abdominal surgery: A case controlled study

Abstract: Background Delta neutrophil index (DNI) can be used as a biomarker for infection to predict patient outcomes. We aimed to investigate the relationship between DNI and clinical outcomes in trauma patients who underwent abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Recently, it was studied as a factor showing the degree of the inflammatory response due to tissue damage or haemorrhage following trauma. Another study conducted in our hospital also revealed that DNI was associated with mortality among patients undergoing surgery due to abdominal trauma [18] . In this study, DNI was not associated with failed CMO in BRI patients.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, it was studied as a factor showing the degree of the inflammatory response due to tissue damage or haemorrhage following trauma. Another study conducted in our hospital also revealed that DNI was associated with mortality among patients undergoing surgery due to abdominal trauma [18] . In this study, DNI was not associated with failed CMO in BRI patients.…”
Section: Discussionmentioning
confidence: 53%
“…There is a difference in DNI between the SIRS group and non-SIRS with a p-value <0.05. Research Bang et al (2020) found there was a significant difference in DNI with postoperative outcomes [30].…”
Section: Resultsmentioning
confidence: 99%
“…The DNI is a numerical value indicating the degree of infection as well as the degree of acute inflammatory response resulting from trauma-induced tissue damage and hemorrhage [21]. Therefore, a higher DNI would be expected in the BUIpresent group, reflecting more severe tissue damage due to BUI, compared with the BUI-absent group.…”
Section: Discussionmentioning
confidence: 99%